Studying the Efficiency of Teaching the Chemical Technology Course Using Information Technologies (Eurasian Journal of Learning and Academic Teaching, 2022)
The article describes in detail the importance of using information technology and the results of the pedagogical effectiveness of teaching chemical technology courses in universities.